1999
DOI: 10.1074/jbc.274.30.21416
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Internalization of the Four Human Leptin Receptor Isoforms

Abstract: There are four known isoforms of the human leptin receptor (HLR) with different C-terminal cytoplasmic domains (designated by the number of unique C-terminal amino acids). In cells expressing HLR-5, -15, or -274, 15-25% of the leptin binding sites were located at the plasma membrane. In contrast, in cells expressing HLR-67, only 5% of the total binding sites were at the plasma membrane. Immunofluorescent microscopy showed that all four isoforms partially co-localized with calnexin and ␤-COP, markers of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
82
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 54 publications
(63 reference statements)
8
82
0
4
Order By: Relevance
“…Little is known about the intracellular trafficking of OB-R (19,21,26,27). We recently showed that OB-R internalizes via a clathrin-mediated pathway and is transported to lysosomes where it is degraded.…”
Section: Regulation Of Ob-r Trafficking By Ob-rgrpmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known about the intracellular trafficking of OB-R (19,21,26,27). We recently showed that OB-R internalizes via a clathrin-mediated pathway and is transported to lysosomes where it is degraded.…”
Section: Regulation Of Ob-r Trafficking By Ob-rgrpmentioning
confidence: 99%
“…We recently showed that OB-R internalizes via a clathrin-mediated pathway and is transported to lysosomes where it is degraded. Most OB-Rs (endogenously expressed or transfected) are localized in intracellular membranes (16)(17)(18)(19)(20)(21)28). Importantly, these receptors are fully functional in terms of ligand binding (19,20).…”
Section: Regulation Of Ob-r Trafficking By Ob-rgrpmentioning
confidence: 99%
See 1 more Smart Citation
“…In human tissues, at least four isoforms of ObR with different COOH-terminal cytoplasmic domains have been described (Barr et al, 1999). The full (long) form of ObR (ObRl) is 1,165 amino acids long (Mr 150,000) and contains the extracellular, transmembrane, and intracellular domain (Fig.…”
Section: Leptin Signalingmentioning
confidence: 99%
“…Ultimately, induction of ObRl can activate several genes involved in cell proliferation, including c-fos, c-jun, junB, egr-1, and socs3, and upregulate the expression angiogenic factors, Fig. 1 (Barr et al, 1999). SRL is a soluble leptin receptor generated by MMPs-mediated shedding of ObRl or ObRs ectodomains.…”
Section: Leptin Signalingmentioning
confidence: 99%